Discourse Enterprise in Natural Resource Management for the Common Heritage of Mankind - Syofyan, Ahmad; Natamiharja, Rudi; Aida, Melly; Aini, Desy Churul; Daryanti, Daryanti; Januarti, Rasti Putri (UI Scholars Hub, 2023)
Common Heritage of Mankind (CHM) is a principle in which all entities can manage the natural resources that exist in the world and must share the benefits of their exploitation with other entities for the common good. However, the principle of CHM has not been structurally and legally regulated in space. The enthusiasm about ‘infinite natural wealth’ that space and seabed mining can produce, particularly in developing countries, means that they can benefit from the activities carried out in order for their regional and mineral resources to be declared as the heritage of mankind. The hypothesis obtained from this research will explore the principles of rules for the management of exploration and exploitation in general of natural resources by international enterprise within the CHM regime and analyze the need to establish management enterprise and international authorities/ organization to manage natural resource exploitation activities as a common heritage. Finding and formulating the urgency of the formation of a business entity and finding a suitable formulation of principles for managing the results of natural resource exploitation activities with international organizations in CHM for international enterprise as business actors who are obliged to have ideas about the mechanisms and procedures in managing Space that has brought out for the exploration and exploitation of the common heritage of mankind. The idea in the International Statute could be the basis for adding a new norm in international law.